(untitled) (Baghdad Science Journal, 2025)
The mutagenic effect of some crucifers widely consumed Lepiduim sativum (Garden cress) and Arugula (Eruca sativa) was studied in comparison to carrot (Daucus carota), using bacterial mutagenic system composed of three bacterial isolates; (Bacillus spp)G3 (Arthrobacter spp)G12, and (Brevibacterium spp)G27 ,. Treatment of isolates with plant extracts led to reduction in survival fraction (Sx)at different levels except that Aurgula extract did not show any inhibitory effect in isolates G12 and G27. Crucifers extracts induced streptomycin resistant mutants in G12 at higher level than G3 , but not in G27. No resistance to rifimpacin was detected in all isolates.